PENGARUH PAJAK DAN KEPEMILIKAN ASING TERHADAP PENERAPAN TRANSFER PRICING PADA PERUSAHAAN MANUFAKTUR SUBSEKTOR MAKANAN DAN MINUMAN YANG TERDAFTAR DI BEI TAHUN 2018-2021 - Herlina Sriyanti; Yoshi Trias Pratiwi (Jurnal Ekonomi, Bisnis dan Social, 2023)
This study aims to analyze the effect of Tax and Foreign Ownership the application to Transfer Pricing in Food and Beverage Subsector Manufacturing Companies Listed on the IDX in 2018-2021. The population in this study amounted to 34 food and beverage subsector companies and by using purposive sampling method through criteria that has been determined, obtained 10 sample companies. The data used are secondary data in form of the company’s annual financial statements for the 2018-2021 reporting period obtained from the IDX website. The data in this study were analyze using a descriptive method using a quantitative approach with the SPSS 26 tool. Based on the results of data analysis using the t test, it is known that the tax variable partially has no effect on the implementation of transfer pricing, while the foreign ownership variable partially affects the implementation of transfer pricing. Meanwhile, based on the results of the analysis using the F test, it is known that the variables of tax and foreign ownership simultaneously affect the application of transfer pricing.